2018
DOI: 10.1126/scitranslmed.aau0713
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy reduces Parkinson’s disease symptoms by reorganizing functional brain connectivity

Abstract: Gene therapy is emerging as a promising approach for treating neurological disorders, including Parkinson’s disease (PD). A phase 2 clinical trial showed that delivering glutamic acid decarboxylase (GAD) into the subthalamic nucleus (STN) of patients with PD had therapeutic effects. To determine the mechanism underlying this response, we analyzed metabolic imaging data from patients who received gene therapy and those randomized to sham surgery, all of whom had been scanned preoperatively and at 6 and 12 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 43 publications
1
74
0
Order By: Relevance
“…Breakthrough research was made by Jinek et al that showed a DNA endonuclease Cas9 guided by two RNAs could introduce target DNA cleavage in vitro (Jinek et al, 2012). From then on, CRISPR/Cas9 technology was developed rapidly and achieved great progress in the field of gene therapy in human CD34 + hematopoietic stem and progenitor cells (HSPCs) (De Ravin et al, 2017; Niethammer et al, 2018). The CRISPR-Cas9 apparatus, involves the Cas9 helicase which can bind to RNA transcribed from the palindromic repeats of host DNA and cleave invasive DNA paired with RNA spacers, a transcript from the short stretches of host DNA acquired from extra chromosomal elements.…”
Section: Crispr/cas9 Technologymentioning
confidence: 99%
“…Breakthrough research was made by Jinek et al that showed a DNA endonuclease Cas9 guided by two RNAs could introduce target DNA cleavage in vitro (Jinek et al, 2012). From then on, CRISPR/Cas9 technology was developed rapidly and achieved great progress in the field of gene therapy in human CD34 + hematopoietic stem and progenitor cells (HSPCs) (De Ravin et al, 2017; Niethammer et al, 2018). The CRISPR-Cas9 apparatus, involves the Cas9 helicase which can bind to RNA transcribed from the palindromic repeats of host DNA and cleave invasive DNA paired with RNA spacers, a transcript from the short stretches of host DNA acquired from extra chromosomal elements.…”
Section: Crispr/cas9 Technologymentioning
confidence: 99%
“…duration 9 years Primary: safety. Well tolerated, no AEs Secondary: improvement in UPDRS, mainly on treated side; reduction in thalamic metabolism on PET on treated side NCT00643890 Sponsor: Neurologix Site: Multicenter Status: Terminated (financial) Duration: 6 months Refs: [ 55 57 ] Long-term f/u: NCT01301573 AAV2-GAD65/GAD67 STN, bilateral Dose: 4.5 × 10 10 vg/STN Infusion: 45 μl/STN iMRI—no Category: phase 2, randomized, sham surgery Patients: 45 patients—split 22/23 (active/sham) Disease stage: advanced PD; avg. duration 10.6/12.0 years Primary: UPDRS scores Secondary: multiple including 18 F-FDG …”
Section: Gene Therapy To Modify Circuitrymentioning
confidence: 99%
“…This strategic failure underlines the high bar to success that exists in the form of STN-DBS, the current gold standard competitor in this therapeutic space. However, this may not be the end of the road for STN-GAD therapy, as a subsequent analysis has emphasized a real and potentially useful effect, with clinical improvements persistent at 12 months and matched by measurable and correlatable changes in network activity as seen with FDG-PET imaging [ 56 , 57 , 60 ]. These later results have yet to salvage the approach, but the technology has now been obtained by another biotech company, MeiraGTx, and is still currently considered to be one of their pipeline products for the treatment of PD.…”
Section: Gene Therapy To Modify Circuitrymentioning
confidence: 99%
“…Although the defense mechanism (Mojica, et al 2009) of bacteria was first observed back in 1987 (Ishino, et al 1987), its possible uses in experiments for scientists has been demonstrated only recently (Jinek, et al 2012) which created a breakthrough for gene editing. Human CD34 + HSPCs were gene edited (De Ravin, et al 2017) by the immensely improving and advancing CRISPR-Cas9 variations and techniques as its progression never even slowed down and more treatment strategies kept appearing (Niethammer, et al 2018). The Cas9 part of the system recognizes and cuts the sequence of DNA/RNA a few base sequences away from the recognized protospacer adjacent motif (PAM) sequence (Hsu, et al 2014).…”
Section: Crispr-cas9 Mediated Systems For Hivmentioning
confidence: 99%